Innovative Practices in Waste Bank Management at Citra Sentosa Mandiri: Praktik Inovatif Pengelolaan Bank Sampah di Citra Sentosa Mandiri - Fikryanita, Nada; Sufyanto, Sufyanto (Indonesian Journal of Law and Economics Review, 2024)
Waste management has become a critical issue in urban communities, necessitating innovative approaches for effective implementation. In Citra Sentosa Mandiri Housing, a waste bank initiative led by community leaders Mr. Agus Irwanto and Mr. Yanto exemplifies a successful model for fostering community engagement in waste management. Despite the growing interest in community-based waste management, there is limited understanding of the role of group communication in facilitating the diffusion of innovation within such contexts. This study aims to analyze communication strategies employed by waste bank activists to disseminate information and assess community adoption and participation in the waste bank program. Utilizing a descriptive qualitative research method and Miles and Huberman's interactive model for data analysis, findings reveal that effective group communication significantly enhances community participation and supports the adoption of waste management innovations. This research contributes to the literature by highlighting the crucial role of communication in transforming community perceptions of waste. The study underscores the importance of structured communication strategies in promoting sustainable waste management practices, providing insights for policymakers and community leaders seeking to implement similar initiatives in other urban settings. Highlights: Effective communication strategies enhance community engagement in waste management. Community leaders play a crucial role in driving waste bank initiatives. Structured communication transforms perceptions of waste within the community. Keywords: Waste Management, Group Communication, Innovation Diffusion, Community Participation, Sustainable Practices